Cost effective natural adsorbent for fluoride removal - S. Janta (2018)
In this study, the uptake of fluoride by raw diatomite and diatomite activated by heat treatment was investigated. Influential parameters such as contact time, pH and adsorption isotherm were also studied. The results showed that the diatomite heated to 500 °C performed better than other heat treatment products and the equilibration time needed for fluoride removal by the adsorbents was reached at 60 min. Results revealed that the capacity of the adsorbents for removing fluoride is independent of the pH when the pH is higher than 4. The adsorption isotherm of the 500°C treated diatomite showed its Langmuir behavior. The maximum adsorption capacity of raw diatomite and 500 °C calcinated diatomite are 2.253 and 4.162 mg/g, respectively. Based on the results it can be concluded that the diatomite appears to be an economical and environmentally friendly material for defluoridation of water. © 2008 Trans Tech Publications, Switzerland.